2016
DOI: 10.12932/ap0752
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and clinical features of anaphylaxis in a developing country: nationwide survey.

Abstract: In Turkey, bee venom was the most common cause of anaphylaxis, followed by food and drug. While more than a half of patients reported recurrent attacks; only 10% had been prescribed epinephrine auto-injector kit after their first episode. Strategies to improve the anaphyalxis management are therefore urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
7
6
0
1
Order By: Relevance
“…In a survey of Russian physicians' knowledge of diagnosis and management of food-induced anaphylaxis, only 29% of those making the correct diagnosis chose epinephrine intramuscular as first line treatment (10% of the responders), while higher percentages preferred intramuscular corticosteroids (37%) or chlorpheniramine (26%) [24] . Similar results were also observed in studies from South Korea [19] , Turkey [25] , Lebanon [26] , while the performance was much better when selected specialties were surveyed including the emergency centre physicians 27. , 28.…”
Section: Discussionsupporting
confidence: 84%
“…In a survey of Russian physicians' knowledge of diagnosis and management of food-induced anaphylaxis, only 29% of those making the correct diagnosis chose epinephrine intramuscular as first line treatment (10% of the responders), while higher percentages preferred intramuscular corticosteroids (37%) or chlorpheniramine (26%) [24] . Similar results were also observed in studies from South Korea [19] , Turkey [25] , Lebanon [26] , while the performance was much better when selected specialties were surveyed including the emergency centre physicians 27. , 28.…”
Section: Discussionsupporting
confidence: 84%
“…A male predominance was identified in our cohort, which is also a frequent finding in previous studies and case series [ 12 , 13 , 14 , 15 ]. In our population, symptoms mainly involved the skin and respiratory system, consistent with previous data [ 1 , 8 , 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…These studies are reported in Fig 2 . 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Resultsunclassified